Creatinine kinase isoenzyme-MB: A simple prognostic biomarker in patients with pulmonary embolism treated with thrombolytic therapy - Bozbay, Mehmet; Uyarel, Huseyin; Avsar, Sahin; Oz, Ahmet; Keskin, Muhammed; Tanik, Veysel Ozan; Bakhshaliyev, NIJAD; BAKHSALIYEV, NIJAD; Ugur, Murat; Pehlivanoglu, Seckin; Eren, Mehmet (My University, 2015)
Background: Creatinine kinase isoenzyme-MB(CK-MB) is a biomarker for detecting myocardial injury. The aim of this study was to evaluate the association between admission CK-MB levels and in-hospital and long-term clinical outcomes in pulmonary embolism(PE) patients treated with thrombolytic tissue-plasminogen activator.